2015
DOI: 10.1007/s11356-015-5707-9
|View full text |Cite
|
Sign up to set email alerts
|

Ecological determinants of health: food and environment on human health

Abstract: Human health and diseases are determined by many complex factors. Health threats from the human-animal-ecosystems interface (HAEI) and zoonotic diseases (zoonoses) impose an increasing risk continuously to public health, from those emerging pathogens transmitted through contact with animals, food, water and contaminated environments. Immense challenges forced on the ecological perspectives on food and the eco-environments, including aquaculture, agriculture and the entire food systems. Impacts of food and eco-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 43 publications
0
33
0
3
Order By: Relevance
“…For example, the landfill problems with food wastes in Hong Kong were over 800 tones per day in 2012 [1]. In fact, FAO concluded that about one third of the food produced in the world for human consumption (around 1.3 billion tones) gets lost or wasted every year [29].…”
Section: Ecological Perspective On Health Determinants Of Food and Enmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, the landfill problems with food wastes in Hong Kong were over 800 tones per day in 2012 [1]. In fact, FAO concluded that about one third of the food produced in the world for human consumption (around 1.3 billion tones) gets lost or wasted every year [29].…”
Section: Ecological Perspective On Health Determinants Of Food and Enmentioning
confidence: 99%
“…From the perspective of old public health to new public health model, and now expanded to the current ecological public health model that aims to improve ecological sustainability by creating conditions with broader perspective and multi-dimensional view on preventing diseases by addressing the root causes of disease [1]. UNESCO stated that a sustainable future with the holistic view of health will be populated by healthy people, living in healthy communities, within the resource opportunities and limits of healthy natural environments, as they are inextricably linked at global scales [13].…”
Section: Reconceptualizing Health Promotion Of Sustainable Diets For mentioning
confidence: 99%
See 2 more Smart Citations
“…Exposure to environmental light [1 •• ], air [2], water [5], and food [6] pollution are a major health concern and with intensified industrialization and urbanization [7], its disease burden is likely to increase in the future. For instance, both, exposure to polluted air as well as changes in the day/night cycle have been described to increase the susceptibility for cardiovascular and metabolic injury.…”
Section: Introductionmentioning
confidence: 99%